2006
DOI: 10.5194/acpd-6-2965-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-model ensemble simulations of tropospheric NO<sub>2</sub> compared with GOME retrievals for the year 2000

Abstract: Abstract. We present a systematic comparison of tropospheric NO2 from 17 global atmospheric chemistry models with three state-of-the-art retrievals from the Global Ozone Monitoring Experiment (GOME) for the year 2000. The models used constant anthropogenic emissions from IIASA/EDGAR3.2 and monthly emissions from biomass burning based on the 1997–2002 average carbon emissions from the Global Fire Emissions Database (GFED). Model output is analyzed at 10:30 local time, close to the overpass time of the ERS-2 sat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 41 publications
6
61
2
Order By: Relevance
“…For combustion sources in winter, the a posteriori inventory indicates an increase of 50% relative to the a priori for north China (100–123°E, 32–42°N), as compared to a 20% increase to the south. Previous studies comparing GOME observations with model results found a similar pattern with NO 2 columns underestimated significantly by model results in winter in the north [ Ma et al , 2006; van Noije et al , 2006; Jaeglé et al , 2005]. The large discrepancy for combustion sources in winter could be attributed to errors in both the bottom‐up and the top‐down approach.…”
Section: Partitioning Of Gome‐derived Emissionssupporting
confidence: 60%
See 3 more Smart Citations
“…For combustion sources in winter, the a posteriori inventory indicates an increase of 50% relative to the a priori for north China (100–123°E, 32–42°N), as compared to a 20% increase to the south. Previous studies comparing GOME observations with model results found a similar pattern with NO 2 columns underestimated significantly by model results in winter in the north [ Ma et al , 2006; van Noije et al , 2006; Jaeglé et al , 2005]. The large discrepancy for combustion sources in winter could be attributed to errors in both the bottom‐up and the top‐down approach.…”
Section: Partitioning Of Gome‐derived Emissionssupporting
confidence: 60%
“…To minimize biases we have treated free parameters in the retrieval in a manner consistent with the CTM; that is, the Dalhousie/SAO retrieval used in our work uses the vertical profile of NO 2 simulated by the GEOS‐Chem model. Among the CTMs and retrievals selected in the intercomparison work of van Noije et al [2006], the variations of simulated and retrieved columns over east China are generally within 20%. The uncertainties assigned in our work to model columns (20%) and retrieved columns (30%) are in agreement with those indicated by van Noije et al [2006].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the detailed model evaluation [ Sudo et al , 2002b], good agreements between the CHASER simulations and observations are generally found for O 3 and precursor species including HO x radicals. The CHASER model performance is also evaluated in the framework of the 4th assessment report of the Intergovernmental Panel on Climate Change (IPCC) [e.g., van Noije et al , 2006].…”
Section: Methodsmentioning
confidence: 99%